The Effectiveness of Microfinance Schemes in Promoting the Sustainability of Micro Enterprises in Developing Countries - Bunga Andini; Mifta Hasda; Muhammad Syaipudin (Global Sustainability Research Institute, 2026)
Introduction: Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, particularly in job creation and strengthening the people's economy. However, limited access to formal financing sources remains a major obstacle hindering MSME performance. Microfinance serves as a crucial instrument for expanding financial inclusion and encouraging microenterprise development. This study aims to analyze the effect of microfinance on MSME performance. Methods: This study used a quantitative approach with a survey of 320 MSMEs who had received microfinance. Data were collected through a structured questionnaire that had been tested for validity and reliability. The sampling technique used purposive sampling, with the criteria being that respondents had received microfinance for at least one year. Data analysis was conducted using multiple linear regression to examine the effect of microfinance on MSME performance. Results: The analysis shows that microfinance has a positive and significant effect on MSME performance. Microfinance has been proven to improve business performance, as reflected in increased revenue, more efficient business management, and business sustainability. The results of the validity and reliability tests indicate that all research indicators meet the required measurement criteria, so the results of the hypothesis testing can be interpreted scientifically and reliably. Conclusion and Suggestion: This study concludes that microfinance is a significant factor in improving MSME performance. Therefore, it is recommended that microfinance institutions and policymakers not only expand microfinance distribution but also improve the quality of financing through schemes tailored to MSME needs and business mentoring support to ensure the sustainable impact of financing.